2020
DOI: 10.1177/1097184x20971023
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Tensions Between Masculinities and Connections with Faculty and Staff among Gay Latino Collegians

Abstract: This study utilizes Gloria E. Anzaldúa’s Border theory to explore how internalized messages of masculinities shape the ways that gay Latino men develop connections with university staff and faculty. Specifically, we highlight how such messages learned primarily in the context of the home create spaces of tension, nepantla, within heteronormative campus settings. We present portraits of five Latino collegians enrolled in a large public four-year institution, followed by three themes. The themes include gay Lati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…It is also important to note that "coming out" takes on many different forms of disclosure for queer Latinx/a/o people such as explicitly naming oneself to others (Eaton & Rios, 2017) or engaging in a tacit subjectivity (Decena, 2011). In addition, one's disclosure can often include negotiating one's cultural and familial values, gender roles, and a care for relationship dynamics with others including family and friends (Acosta, 2010;Duran & Pérez, 2017;Orozco & Pérez-Felkner, 2018;Patro ´n & Rodriguez, 2022;Vega et al, 2023). Conversely, the constant negotiation of their queer Latinx/a/o realities complicates how individuals perceive and engage with familial relationships including chosen kinships with peers (Acosta, 2010;Duran & Pérez, 2017;Patro ´n, 2021aPatro ´n, , 2021b.…”
Section: Queer Latinx/a/o Identity Development and Negotiationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to note that "coming out" takes on many different forms of disclosure for queer Latinx/a/o people such as explicitly naming oneself to others (Eaton & Rios, 2017) or engaging in a tacit subjectivity (Decena, 2011). In addition, one's disclosure can often include negotiating one's cultural and familial values, gender roles, and a care for relationship dynamics with others including family and friends (Acosta, 2010;Duran & Pérez, 2017;Orozco & Pérez-Felkner, 2018;Patro ´n & Rodriguez, 2022;Vega et al, 2023). Conversely, the constant negotiation of their queer Latinx/a/o realities complicates how individuals perceive and engage with familial relationships including chosen kinships with peers (Acosta, 2010;Duran & Pérez, 2017;Patro ´n, 2021aPatro ´n, , 2021b.…”
Section: Queer Latinx/a/o Identity Development and Negotiationmentioning
confidence: 99%
“…Similarly, Peña-Talamantes (2013) examined how lesbian Latinas and gay Latinos negotiated their sexual and ethnic identities within the college environment and their hometowns to maintain a sense of freedom, security, and belonging among themselves and their respective families. The support that students receive on campus from peers, staff, and faculty (Duran & Pérez, 2017; Patrón & Rodriguez, 2022; Peña-Talamantes, 2013) often serves as a buffer or added support system from the silence or invisible realities with their families when they choose to disclose or not disclose their sexualities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This may then have implications across contexts. For instance, Patrón and Rodriguez (2020) found that internalized messages of masculinity learned in the home may transfer to the university setting, affecting the ways gay Latinos connect with faculty and staff. Relatedly, Morales (1989) shared that while family is the “emotional bond for the conscious self and personal psychology” (p. 233), it can jeopardize intra-family relationships for “minority lesbians and gays.” Although familial rejection of sexually marginalized individuals could affect everyone regardless of gender, literature has primarily focused on men (e.g., Eaton & Rios, 2017; Li et al, 2017; Ocampo, 2014).…”
Section: Queer Latinas/os/xs and Familymentioning
confidence: 99%
“…In order to prevent familial conflict, some queer individuals may decide to live a double life where they present in one way in front of their families and in another outside of that setting, may be more strategic in the coming out process to family, or decide to keep their sexualities hidden (Acosta, 2008, 2013; Guarnero & Flaskerud, 2008; Ocampo, 2014; Patrón & Rodriguez, 2020). Suppressing their queer identity, however, may be linked with emotional distress.…”
Section: Queer Latinas/os/xs and Familymentioning
confidence: 99%